Nonoperative Management of Spinal Epidural Abscess: Development of a Predictive Algorithm for Failure - Shah, Akash A; Ogink, Paul T; Nelson, Sandra B; Harris, Mitchel B; Schwab, Joseph H (Journal of bone and joint surgery. American volume, 2018)
Prompt diagnosis and treatment are critical in spinal epidural abscess, as delay can lead to paralysis or death. The initial management decision for spinal epidural abscess is not always clear, with the literature showing conflicting results. When considering nonoperative management, it is crucial to avoid failure of treatment, given the neurologic compromise incurred through failure. Unfortunately, data regarding risk factors associated with failure are scarce. All patients admitted to our hospital system with a diagnosis of spinal epidural abscess from 1993 to 2016 were identified. Patients who were ≥18 years of age and were initially managed nonoperatively were included. Explanatory variables and outcomes were collected retrospectively. Bivariate and multivariable analyses were performed on these variables to identify independent predictors of failure of nonoperative treatment. A nomogram was constructed to generate a risk of failure based on these predictors. We identified 367 patients who initially underwent nonoperative management. Of these, 99 patients underwent medical management that failed. Multivariable logistic regression yielded 6 independent predictors of failure: a presenting motor deficit, pathologic or compression fracture in affected levels, active malignancy, diabetes mellitus, sensory changes, and dorsal location of abscess. We constructed a nomogram that generates a probability of failure based on the presence of these factors. By quantifying the risk of failure on the basis of the presence of 6 independent predictors of treatment failure, our nomogram may provide a useful tool for the treatment team when weighing the risks and benefits of initial nonoperative treatment compared with operative management. Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.